PENYULUHAN TENTANG MANFAAT PIJAT OKSITOSIN DI DESA ULE PATA KECAMATAN JAYA BARU BANDA ACEH - Martina; Zuhkrina, Yuli; Amalia, Shinta; Zulbaini, Angela; Maulida; Nurlaila; Anggraini, Pipit Novel (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2020)
The decrease in the achievement of exclusive breastfeeding is influenced by several factors, including reduced milk production caused by hormones and the mother's perception of insufficient breast milk. The production and expenditure of breast milk in the body is influenced by two hormones, namely prolactin and oxytocin. To overcome the problem of breast milk production caused by decreased stimulation of the oxytocin hormone, namely by breastfeeding early in the first hours because the nipples are often sucked by the baby's mouth, the more hormones are produced, so that more milk comes out. In addition, oxytocin massage can also be done. This action can help maximize the production of oxytocin, the prolactin receptor and minimize the side effects of delayed breastfeeding by the baby. Efforts to stimulate prolactin and oxytocin hormones in the mother after giving birth other than expressing breast milk can be done by doing breast care or massage, cleaning the nipples, breastfeeding the baby often even though the milk has not come out, early and regular breastfeeding and oxytocin massage. For some mothers, it may be difficult to express breast milk, but more mothers are influenced by myths so that mothers are not sure that they can give breast milk to their babies. The feeling of the mother who is not sure that she can give breast milk to her baby will cause a decrease in the hormone oxytocin so that milk cannot come out immediately after giving birth and finally the mother decides to give formula milk to her baby often breastfeed the baby even though the milk has not come out, early and regular breastfeeding and oxytocin massage. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of the benefits of oxytocin massage, which was in the good category as much as 26 (63.4%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling.